Novel approach to breathable nonwoven hygienic products - (:unkn) unknown (WOODHEAD PUBL LTD, 2006)
Cost contribution of nonwoven materials in hygiene products such as baby's nappies is about 10%. One of the main contributors to the cost in breathable nappies is the breathable sheet. The advantages of breathable nappies are in fact to reduce problems caused by babies skin not being able to get air i.e. nappy rash etc. Moving from this idea of using nonwoven products instead of polyethylene film, which will not pass liquid outside but yet will give some form of breathability, was the main start point of this project. For this work various nonwoven products have been treated with water repellent chemicals and tested for water repellence as well as the tenacity and extensibility etc.
Keywords: nonwoven; hygienic; baby nappy; breathable; water repellent; chemicals; tenacity; extensibility